Abundance and reproduction of brown pelican (Pelecanus occidentalis) in two bays in the Mexican central Pacific - Hernández-Vázquez, Salvador; Iñigo-Elias, Eduardo; Hinojosa Larios, J. Ángel; Durand Martínez, Braulio; Rojo-Vázquez, J. A.; Valadez González, Carmen (Instituto de Ecología, A.C., 2011)
The abundance and reproduction of the brown pelican (Pelecanus occidentalis) was studied in two bays of the Mexican Central Pacific, Bahía de Navidad and Bahía Chamela, located in the coast of Jalisco, Mexico. The number of brown pelicans in both bays was registered from December 2007 to November 2009, as well as the number of nests, eggs and nestlings in the Cocinas Island. The superficial temperature of the water, the nutrients (NO2 -, NO3-, NH4 + y PO4 -) and the primary productivity (clorofile a) were measured on a monthly basis. The greater number of pelicans was registered from January to March, in both bays. There were a bigger number of birds in the Chamela bay, mainly in early 2009. The reproductive period of the brown pelican extended from December to July on both years. The largest number of nests was observed in March and April, with an estimate of 480 (90.7 nests/hectares) in the whole nesting season of 2008 and 1,200 (226.8 nests/hectares) in 2009. In 2008 there were an estimate 1,310 eggs and 800 nestlings, while in 2009 there were an estimate 3,348 eggs and 2,200 nestlings. Both, the highest number of birds, as well as the highest number of nests, eggs and nestlings registered in 2009 were present when the temperature of the water registered its lowest values and the primary productivity (clorofile a) and nutrients, mainly NO3 - and PO4 -, registered their highest levels. These variables have a direct effect in the concentration of a larger number of fish.